A live imaging‐friendly slice culture method using collagen membranes - Ari Ogaki; Tasuku Araki; Masaya Ishikawa; Yuji Ikegaya; Ryuta Koyama (Wiley, 2020)
Abstract Aim Organotypic brain slice culture preserves the geographical position of neurons and neuronal circuits. The slice cultures also maintain both non‐neuronal cell types and the surrounding extracellular matrix. The interface method has been widely used for slice cultures, in which brain slices are placed on semiporous polytetrafluoroethylene (PTFE) membranes. However, a low optical transparency of PTFE membrane makes it difficult to perform live imaging of deep regions of slice cultures using an inverted microscope. To overcome the issue, we evaluated the suitability of using collagen membranes for slice cultures, especially focusing on live imaging of the cellular dynamics of green fluorescent protein (GFP)‐expressing microglia. Methods Entorhinohippocampal slices were cultured on either collagen or PTFE membranes. The influence of membrane type on the ability to observe deep regions of slice cultures was examined by live imaging using an inverted microscope. Results Collagen membranes were thinner and had better optical transparency compared with PTFE membranes. There were no differences in cell viability, density of neurons or microglia. The densify of visible short branches of microglia in live imaging was higher in collagen membranes than PTFE membranes. Conclusion Collagen membranes are suitable for live imaging of cellular dynamics in slice cultures using an inverted microscope.